QUALIDADE NUTRICIONAL DE CAPIM SUDÃO SUBMETIDO À DIFERENTES FONTES NITROGENADAS - DOS SANTOS CARDOSO , JAÍNE; ANDRÉ PEREIRA , EMERSON; DE OLIVEIRA KULINSKI , CAMILA; DOS SANTOS CARGNELUTTI , CAROLINA; ENDERLI DO NASCIMENTO , JÚLIA; MIHLBEIER BONFADA , BRUNO (Salão do Conhecimento, 2021)
Jaíne dos Santos Cardoso, Emerson André Pereira, Camila de Oliveira Kulinski , Carolina dos Santos Cargnelutti , Júlia Enderli do Nascimento, Bruno Mihlbeier Bonfada